Reparation for Damages Resulting from Genetically Modified Foods - Radeef, Yusra A. (Jurnal Perilaku Kesehatan Terpadu, 2024)
Genetically modified organisms (GMOs) have revolutionized agriculture, offering the potential for enhanced food production, improved nutritional content, and resistance to diseases. As the global demand for food increases, biotechnology and genetic engineering have emerged as essential tools to address food scarcity. The rapid development of these technologies has led to the widespread use of genetically modified crops, making it necessary to adopt efficient methods for detecting GMOs in food products. This study explores various detection techniques for GM foods, focusing on the application of Polymerase Chain Reaction (PCR), Capillary Gel Electrophoresis (CGE), Enzyme-Linked Immunosorbent Assay (ELISA), Next-Generation Sequencing (NGS), and biosensors. While PCR remains the gold standard for GMO detection, advances such as multiplex PCR, CRISPR-based methods, and NGS offer enhanced sensitivity and specificity, allowing for the detection of multiple GM traits and minimizing false positives and negatives. Biosensors, particularly DNA-based systems, provide a rapid, cost-effective, and portable option for on-site detection, while NGS offers a comprehensive approach to analyze entire genomes. This paper reviews the strengths, limitations, and applications of these methods, discusses their integration for improved accuracy, and highlights their role in regulatory compliance and ensuring food safety. Ultimately, the integration of these advanced techniques promises a robust solution for GMO detection, supporting regulatory authorities in monitoring and labeling GM foods, safeguarding public health, and enhancing transparency in the food supply chain.